Approaching Clinical Data Transformation from Disparate Healthcare IT Systems Through a Modular Framework. - Phan-Vogtmann, Lo An; Helhorn, Alexander; Kruse, Henner M.; Thomas, Eric; Heidel, Andrew J.; Saleh, Kutaiba; Rissner, F.; Specht, Martin; Henkel, Andreas; Scherag , André (Studies in Health Technology and Informatics, 2019)
Many healthcare IT systems in Germany are unable to interoperate with other systems through standardised data formats. Therefore it is difficult to store and retrieve data and to establish a systematic collection of data with provenance across systems and even healthcare institutions. We outline the concept for a Transformation Pipeline that can act as a processor for proprietary medical data formats from multiple sources. Through a modular construction, the pipeline relies on different data extraction and data enrichment modules as well as on interfaces to external definitions for interoperability standards. The developed solution is extendable and reusable, enabling data transformation independent from current format definitions and entailing the opportunity of collaboration with other research groups.